Вплив індустрії 4.0 на характеристики системи управління ланцюгами постачань - Щербань, О. Д.; Shcherban, O. D. (Університет економіки і підприємництва, 2025)
Дослідження аналізує вплив Індустрії 4.0 на трансформацію ключових характеристик систем управління ланцюгами поставок (СУЛП). Під дією технологій (кіберфізичні системи, IoT, Big Data, ШІ) СУЛП еволюціонують від лінійних моделей до гнучких, адаптивних мереж з підвищеною прозорістю та інтегрованістю. Робота зосереджена на 4 логістичних сферах: закупівлі, транспорт, склад, виконання замовлень. Для кожної визначено ключові показники ефективності (КРІ) та детально досліджено, як технології І4.0 змінюють ці КРІ, формуючи нові характеристики (прозорість, адаптивність, інтероперабельність, ефективність, резильєнтність, інноваційність). Запропоновано інноваційний підхід оцінки через «описовий профіль характеристик СУЛП», який замість жорстких матриць дозволяє визначати поточний стан, цільові рівні, драйвери змін та ризики для кожної характеристики. Цей профіль є інструментом для виявлення «вузьких місць», пріоритезації інвестицій у цифрові рішення (IoT-платформи, блокчейн) та формування стратегій трансформації. Висновок: цифровізація СУЛП є ключем до підвищення клієнтоорієнтованості, оптимізації витрат і адаптації до швидкозмінного ринку в епоху Індустрії 4.0.

This study examines the transformative impact of Industry 4.0 (I4.0) technologies on the core characteristics of Supply Chain Management (SCM) systems. Driven by cyber-physical systems (CPS), the Internet of Things (IoT), Big Data analytics, Artificial Intelligence (AI), cloud computing, and robotics, traditional linear and stable SCM models are evolving into hyper-connected, agile, and intelligent networks. The research focuses on the logistical dimensions of SCM: Procurement, Transportation, Warehousing, and Order Fulfillment. For each functional area, critical Key Performance Indicators (KPIs) are identified and justified, serving as quantitative measures of characteristics like speed, accuracy, cost efficiency, flexibility, reliability, and customer-centricity. The core contribution lies in a systematic analysis of how specific I4.0 technologies impact these KPIs within each SCM function. For instance: CPS/IoT enable unprecedented end-to-end visibility and real-time tracking of assets/ orders. Big Data & AI facilitate predictive analytics for demand forecasting, route optimization, and proactive issue resolution, enhancing agility and responsiveness. Robotics & Automation (e.g., autonomous guided vehicles, smart warehouses) significantly improve speed and accuracy in warehousing and fulfillment. Additive Manufacturing (3D Printing) influences localization and customization potential, impacting supply chain structure. Cloud Computing & Interoperability Standards (APIs, blockchain) underpin seamless data exchange (interoperability) across the network. Recognizing the limitations of rigid assessment matrices, the study proposes a novel "Descriptive SCM Characteristics Profile" framework. This dynamic framework enables managers to: Identify critical bottlenecks ("weakest" characteristics). Prioritize digital investments based on potential impact on target characteristics/KPIs. Develop actionable roadmaps combining technology implementation (e.g., IoT platforms, AI controllers) with organizational process changes. Track progress through regular KPI measurement against targets. The study concludes that digital transformation, guided by this characteristics-centric approach, is essential for SCM systems to achieve superior customer orientation, optimize costs across the chain, enhance resilience, and maintain competitiveness in the dynamic global market shaped by Industry 4.0.
Impact of industry 4.0 on the characteristics of the supply chain management system
Keywords: інформаційні технології; логістика; система управління ланцюгами поставок; цифрова економіка; ключові показники ефективності; Індустрія 4.0. information technology; logistics; supply chain management system; digital economy; key performance indicators; Industry 4.0.